"Aus grossen fragenden Augen schaut Krankheit und frühes Wissen um Elend und Not."
internationale Politik (allgemein);internationale Beziehungen;Entwicklungszusammenarbeit;Hilfswerk soziale Fragen;Leben in der Gesellschaft (allgemein);soziales Problem;Armut